2016
DOI: 10.17077/2154-4751.1325
|View full text |Cite
|
Sign up to set email alerts
|

Demographic profile and treatment outcomes of 100 women with obstetric fistula in Niger

Abstract: Abstract:Introduction: Due to high fertility rates, low access to emergency obstetric care, and the poor quality of that care, obstetric fistula is relatively widespread in Niger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Following the selection and quality appraisal phases, 79 studies were transferred to the systematic review and meta-analysis phases to determine the pooled proportion of successful surgical repairs of obstetric fistulae and to identify the determinants of successful surgical repair. The minimum proportion of successful recovery, 36%, was reported by Heller et al [ 59 ] in Niger, and a 100% recovery was reported by Sharma et al [ 46 ] in India. The pooled proportion of successful surgical repair of obstetric fistula was determined by meta-analysis among 76 studies, excluding the study by Sharma et al [ 46 ] to avoid the undue outlier effect of 100% recovery.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Following the selection and quality appraisal phases, 79 studies were transferred to the systematic review and meta-analysis phases to determine the pooled proportion of successful surgical repairs of obstetric fistulae and to identify the determinants of successful surgical repair. The minimum proportion of successful recovery, 36%, was reported by Heller et al [ 59 ] in Niger, and a 100% recovery was reported by Sharma et al [ 46 ] in India. The pooled proportion of successful surgical repair of obstetric fistula was determined by meta-analysis among 76 studies, excluding the study by Sharma et al [ 46 ] to avoid the undue outlier effect of 100% recovery.…”
Section: Resultsmentioning
confidence: 91%
“…proportion of successful recovery, 36%, was reported by Heller et al [59] in Niger, and a 100% recovery was reported by Sharma et al [46] in India. The pooled proportion of successful surgical repair of obstetric fistula was determined by meta-analysis among 76 studies, excluding the study by Sharma et al [46] to avoid the undue outlier effect of 100% recovery.…”
Section: Plos Onementioning
confidence: 77%
See 2 more Smart Citations
“…Bladder stones cause women abdominal pain and painful urination (as well as more serious health problems), and often must be surgically removed before women are able to undergo fistula repair surgeries. In the neoliberal healthcare terrain of Niamey, within which fistula care is commoditized and outsourced to visiting teams of foreign surgeons, the women I interviewed waited an average of six months and up to six years on hospital grounds to receive operations (see Heller 2017). Surgeries were maddeningly infrequent; long waits and protracted absences from home had serious consequences on women's social lives, often resulting in divorce and the attenuation of social bonds.…”
Section: The Price Of Passingmentioning
confidence: 99%